A synthesis of constructs for modelling consumers’ perception of value from mobile-commerce (M-VAL) - Dastane, Omkar; Goi, Chai Lee; Rabbanee, Fazlul (Elsevier, 2020)
Customer Perceived Value (CPV) is a well-established concept in the marketing literature; however, there is a need to extend the concept of Perceived Value (PV) to mobile shopping consumers. Meanwhile, the synthesis of construct, dimensionality, and modelling of PV in the context of mobile shopping only received scant attention despite the efforts in conceptualising and testing various PV elements for a range of businesses. Hence, a definite contribution to the existing literature is by structuring the themes based on related approaches. Accordingly, the present study conducted a systematic and comprehensive review of perceived value literature on mobile shopping obtained from the Scopus database. Next, all the possible factors from recent literature were synthesised in the current research for the purpose of measuring the perception of value on mobile commerce (M-VAL). Finally, a framework of ten parameters was successfully established and can be used as a reference for future research. Overall, the tentative yet inclusive set of parameters is deemed useful in designing future empirical researches that aim to develop a multidimensional multi-item scale to measure M-VAL.